Penerapan Teknologi Pencetakan 3D dalam Penciptaan Aksesori Fesyen Inovatif - Kristanti Kristanti; Noor Laila Ramadhani; Bulan Karima Nurani (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2026)
3D printing technology offers new opportunities in the fashion world, particularly in accessory production. This method allows designers to create complex, detailed, and unique shapes that are difficult to achieve with conventional techniques. The materials used vary, from plastic and resin to environmentally friendly bio-based filaments. The main advantages of 3D printing are design flexibility, production efficiency, and the ability to personalize products according to consumer needs. This allows for the creation of fashion accessories that are not only aesthetic but also functional, such as jewelry, bags, glasses, and decorative elements for clothing. Furthermore, 3D printing supports the principles of sustainable fashion, as it can reduce production waste by only printing what is needed. Overall, the application of 3D printing in fashion accessories paves the way for innovation, sustainability, and individuality, while expanding the boundaries of designer creativity in the fashion industry. Objective Research: aims to explore 3D printing technology in creating fashion accessories. and the sustainability of aesthetic value, functionality, and innovation of 3D printing-based fashion accessory products. Thus, this research will provide important insights for industry players in designing business strategies that are not only profitable, but also reduce production waste, which is expected to increase competitiveness and long-term sustainability. The research method uses a systematic approach to problem-solving that focuses on a deep understanding of user needs and experiences. This method combines creativity and analysis to produce innovative and effective solutions. These findings are expected to make a significant contribution to the development of 3D printing-based fashion accessory products and offer strategic solutions for fashion industry players paving the way towards innovation, sustainability and individuality, while expanding the boundaries of designer creativity in the fashion industry.